Leveraging customer knowledge: a comparative study of eCRM functionality and its use in e-commerce websites. (19th June 2008) - Kim, Yong-Mi; Hawamdeh, Suliman
Customer knowledge is recognised as a source of innovation and a key strategic resource. Effective management of customer knowledge helps organisations to understand customer needs, increase customer satisfaction and loyalty, as well as maintain competitive advantages. In the online environment and in the absence of face to face interaction with customers, organisations are turning to modern information technology tools to help better manage customer knowledge and customer relations. In this paper, we explore and investigate how companies make use of eCRM functionality to attract and retain customers as well as leverage customer knowledge.